2009
DOI: 10.1016/j.rmed.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbations in subjects with alpha-1 antitrypsin deficiency receiving augmentation therapy

Abstract: COPD exacerbations occur frequently and are associated with significant disease burden in subjects with AATD receiving augmentation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 25 publications
4
39
0
4
Order By: Relevance
“…Interestingly, the results observed in the previously mentioned studies in individuals with COPD www.copdjournal.com associated with AATD were similar to those obtained in previous studies in non-AATD COPD. Th e scores of the SGRQ were worse in patients experiencing frequent exacerbations, either while on augmentation therapy (23) or not (24). Th e scores of the SGRQ were also worse in patients with more severe impairment in lung function, as observed in non-AATD COPD (24), and more interestingly, the changes in SGRQ scores correlated with changes in lung density over time (25), suggesting that monitoring health status would be a good way of monitoring the progression of the disease in patients with emphysema due to AATD.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the results observed in the previously mentioned studies in individuals with COPD www.copdjournal.com associated with AATD were similar to those obtained in previous studies in non-AATD COPD. Th e scores of the SGRQ were worse in patients experiencing frequent exacerbations, either while on augmentation therapy (23) or not (24). Th e scores of the SGRQ were also worse in patients with more severe impairment in lung function, as observed in non-AATD COPD (24), and more interestingly, the changes in SGRQ scores correlated with changes in lung density over time (25), suggesting that monitoring health status would be a good way of monitoring the progression of the disease in patients with emphysema due to AATD.…”
Section: Discussionmentioning
confidence: 96%
“…Augmentation therapy was FDA approved and is now widely used in Europe and North America in the treatment of AATD individuals with lung disease (Abboud et al 2001). Documented studies on the clinical efficiency of infused AAT augmentation therapy have reported on patient outcome measures including the rate of decline in forced expiratory volume in one second (FEV 1 ) (Seersholm et al 1997;Wencker et al 2001), the incidence of acute exacerbations (Campos et al 2009) and the change in lung density (Dirksen et al 1999) calculated by computed tomography scanning (Dirksen et al 2009). …”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Lung Dismentioning
confidence: 99%
“…Reduced exacerbations or lung infections is an important endpoint in clinical studies of pulmonary disease and recent data from a German AATD registry (455 with the ZZ and SZ genotype) suggests that a reduction of exacerbations is directly associated with health-related quality of life of patients (Koczulla et al 2008). Clinicians have attempted to address this important endpoint (Campos et al 2009;Lieberman 2000;Needham and Stockley 2005) with Lieberman (2000) conducting an internet survey of patient-reported respiratory infections in individuals with the ZZ phenotype, which were markedly decreased after the introduction of augmentation therapy (Lieberman 2000). Post hoc analysis of the EXACTLE study, adjusted for exacerbation severity showed that the treatment group had fewer severe exacerbations than the control group.…”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Lung Dismentioning
confidence: 99%
“…The global dysfunction of AM engulfment in smokers and COPD patients may be most damaging during acute infectious exacerbations, episodes of increased airway infection and inflammation during which AM have to scavenge an increased load of both bacterial and apoptotic targets [3]. Given the high morbidity and mortality, as well as healthcare cost associated with COPD and COPD exacerbations [4, 5], therapies aimed at improving AM scavenging functions are of clinical importance.…”
Section: Introductionmentioning
confidence: 99%